First-principles calculations of structural, elastic, electronic, and optical properties of perovskite-type KMgH3 crystals: Novel hydrogen storage material - Ali Hussain, Reshak, Prof. Dr.; Mikhail Y., Shalaginov; Yasir, Saeed; Kityk, I. V.; Auluck, S. (American Chemical Society, 2011)
Link to publisher's homepage at http://www.acs.org/